PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI (Studi pada PT. Pinnacle Apparels Semarang) - Suci Nurul Hidayah, 13.05.51.0026; Priyono, Bambang Suko (Students' Journal of Economic and Management, 2017)
The purpose of this study is to find the influence of style leadership , motivation and compensation of the performance of employees at PT. Pinnacle Apparels Semarang.The research uses a method of survey with the questionnaire as a means of data collection.Population in this study performance employees in PT. Pinnacle Apparels.Technique the sample collection with accidental sampling were 100.Technique data analysis used with linear regression multiple.The research results show that style leadership have had a positive impact and significant of the performance of employees, motivation have had a positive impact and significant of the performance of employees, compensation have had a positive impact and significant of the performance of employees. Keywords: style leadership, motivation, compensation, the employee performance .